Ethnic differences in dentofacial relationships of Turkish and Saudi young adults with normal occlusions and well-balanced faces - Tancan Uysal; Ahmet Yagci; Abdullah M. Aldrees; Esra Ekizer (Elsevier, 2011)
Objectives: The aims of the present study were (1) to determine ethnic differences in craniofacial dimensions between Turkish and Saudi populations and (2) to identify possible gender differences between males and females, based on a sample of untreated young adult subjects with normal occlusions and well-balanced faces. Methods: In total, 163 cephalometric radiographs were traced and evaluated to compare untreated adults of Turkish and Saudi ethnicity. The Turkish group comprised 86 subjects; 45 females and 41 males. The Saudi group comprised 77 subjects; 39 females and 38 males. For statistical evaluation, an independent-samples t-test was performed. Results: The Turkish sample had a more retrognathic maxilla and mandible (p < 0.001 for SNA and SNB) and a more vertical direction of facial development (p < 0.001), with Turkish males having more retrusive lips (p < 0.001). Distinctive ethnic differences were found in craniofacial structures between Turkish and Saudi young adults. Conclusions: It is appropriate to consider these aesthetic differences when a Turkish or a Saudi patient is being evaluated during routine diagnosis and treatment planning. Keywords: Cephalometric norm, Turkish, Saudi, Ethnicity